Ex‐vivo fluorescence confocal microscopy with digital staining for characterizing basal cell carcinoma on frozen sections: A comparison with histology. Issue 8 (24th May 2021) - Ruini, Cristel; Vladimirova, Gabriela; Kendziora, Benjamin; Salzer, Suzanna; Ergun, Ecem; Sattler, Elke; French, Lars E.; Hartmann, Daniela
Abstract: Ex‐vivo fluorescence confocal microscopy (FCM) has been used on fresh tissue, but there is little experience on frozen sections. We evaluated the applicability of FCM on frozen sections of basal cell carcinomas (BCCs), stained with acridine orange and digitally colored to simulate hematoxylin and eosin (H&E) dyes. We compared our diagnostic accuracy in detecting and subtyping BCCs with FCM to our gold standard (H&E stained frozen sections used in 3D horizontal micrographic surgery). Fourty‐six primary BCCs were analyzed for free margins as well as histological subtype with all FCM modes and conventional H&E staining. Adnexa, artifacts and diagnostic confidence were evaluated. Free margins were identified with a sensitivity and specificity of 92% and 91%. Concordance for tumor subtype was 88%. FCM may be used on both fresh tissue and frozen samples, although with reduced performance and different artifacts. The device is useful for the intraoperative diagnosis, subtyping and margin‐mapping of BCCs. Abstract : The introduction of digital staining in ex‐vivo confocal microscopy allows a more intuitive comparison with hematoxylin and eosin stained conventional histology. This pilot study on basal cell carcinoma and frozen sections highlights the diagnostic potential of this new technique to support bedside surgery.